Interactions Between Paracetamol and Hypromellose in the Solid State - Leyk, Edyta; Wesolowski, Marek (Frontiers in Pharmacology, 2019)
Hydroxypropyl methylcellulose (hypromellose) is a widely known excipient commonly used in the preparation of drug formulations. It can interact with some active pharmaceutical ingredients (APIs), thereby contributing to a reduction in crystallinity, serve as a solvent for API or form stable dispersion with no tendency to aggregation. The aim of the present study was to investigate the effect of hypromellose on the solubility, miscibility and amorphization of paracetamol in mixture with this polymer. Homogenized mixtures of paracetamol with hypromellose were studied using differential scanning calorimetry (DSC), hot-stage microscopy (HSM), Fourier transform infrared (FTIR) and Raman methods to obtain a deeper insight into the interactions between ingredients in solid state including phase diagram construction for crystalline API and amorphous polymer. A DSC study revealed potential interaction between ingredients resulting in reduced paracetamol crystallinity. This was proved using heating-cooling-heating test to confirm paracetamol amorphization. FTIR and Raman investigations excluded chemical reaction and hydrogen bonding between ingredients. The phase diagram developed facilitates predictions on the solubility of API in polymer, on the mutual miscibility of ingredients and on the temperature of mixture glass transition.